Use of AED Levels by Pediatric Neurologists - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Replies from 56 of 60 pediatric neurologists surveyed regarding the use and value of antiepileptic drug (AED) levels were evaluated in the Departments of Pediatrics and Toxicology, Dalhousie University and The IWK Children's Hospital, Halifax, Canada.